PERAN BAWASLU DALAM PENGAWASAN DAN PENINDAKAN PELANGGARAN ADMINISTRASI PEMILU MELALUI MEDIA SOSIAL: ANALISIS YURIDIS NORMATIF DI KABUPATEN PINRANG - Maulana, Arif; Rahman, Ali; Firmansyah, Muhammad; Paratama, Faradillah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The General Election Supervisory Agency (Bawaslu) is given authority based on Law Number 7 of 2017, which has been amended by Law Number 1 of 2022 concerning Amendments to Law Number 7 of 2017 concerning General Elections, to carry out the function of supervision and enforcement of violations of election administration by election participants and their campaign teams. This research is a type of normative juridical research that is descriptive analysis. The Bawaslu of Pinrang Regency identified the supervision of election campaigns through social media due to the high number of violations committed by the State Civil Apparatus (ASN) who campaigned through the platform. Furthermore, the Pinrang Regency Bawaslu carried out actions which are a series of actions to handle election violations in accordance with the standard operating procedures (SOP) that have been set. The handling of violations committed by the Pinrang Regency Bawaslu is through the Integrated Law Enforcement Center (Gakkumdu), which consists of the Bawaslu, the Police, and the Prosecutor's Office. This institution processes and filters existing data, then clarifies relevant parties and decides whether the election participants violated the election or not. Bawaslu has a very important role as an authorized institution in preventing election violations